2007
DOI: 10.1016/j.econlet.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Is the inflation–output Nexus asymmetric in the Euro area?

Abstract: * We are grateful to Cécile Simon for her remarkable assistance and Jean-Guillaume Sahuc for his helpful comments. We also thank J.-M. Charpin who discussed in October 2002 a preliminary version of this paper at the Banque de France workshop chaired by M.-O. Strauss-Kahn. All remaining errors are ours. The views expressed herein are those of the authors and do not necessarily reflect those of the Banque de France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…The early studies working on euro area aggregate data in the 2000s may face, in our view, the problem that they employ synthetic area aggregate data, often going back to the 1970s, as in Aguiar and Martins (), Baghli et al . () and Musso et al . ().…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The early studies working on euro area aggregate data in the 2000s may face, in our view, the problem that they employ synthetic area aggregate data, often going back to the 1970s, as in Aguiar and Martins (), Baghli et al . () and Musso et al . ().…”
Section: Introductionmentioning
confidence: 89%
“…in Hasanov, Arac and Telatar (2010), Musso, Stracca and van Dijk (2009), Huh, Lee and Lee (2009), Huh and Jang (2007, and Telatar and Hasanov (2006). A third group, not that sizable, has considered the use of non-parametric and semiparametric methods, involving Kernel regression methods, as in Buchmann (2009) and Baghli, Cahn and Fraisse (2007). Most analyses, irrespective of the econometric methods employed, used time series data, possibly involving multi-country datasets, but in general did not consider explicit panel methods.…”
Section: Introductionmentioning
confidence: 99%
“…Similar mixed results are reported for European countries. For example, Dolado et al (2005) and Baghli et al (2007) provide some evidence for the relevance of non-linearity in the euro area Phillips curve, while Musso et al (2007) find no significant evidence of non-linearity. curve in excess supply situations differs from that in excess demand situations.…”
Section: Introductionmentioning
confidence: 99%
“…in a similar manner to the accent nonlinear nature of the Philips Curve but in this paper, we do not discuss the justification of these two views. Some papers discussed the nonlinear Phillips Curve such as Eliasson (2001), Baghli, Christophe, and Henri (2007) and Huh, Lee, and Lee (2008), Greenwood-Nimmo, Van Treeck (2011), Xu, Niu, Jiang, andHuang (2015), Bildirici and Ozaksoy (2017), Donayre and Panovska (2016), Bildirici and Turkmen (2016), Zhang (2017). Eliasson (2001) tested a smooth transition model for Australia, the U.S.A. and Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…Huh et al (2008) analysed an LSTAR model and determined the evidence in support of nonlinearity in the U.S.A. P.C. Baghli et al (2007) showed the evidence of nonlinearity in Europe both at the national level and an aggregate level for Germany, Italy and France. Xu et al (2015) (2017) estimated the nonlinear structure of P.C.…”
Section: Introductionmentioning
confidence: 99%